PENGEMBANGAN INSTRUMEN EVALUASI PEMBELAJARAN MENGGUNAKAN APLIKASI QUIZIZZ UNTUK MENGUKUR KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS 5 SDN INPRES PARADOWANE - Muhammad Nilwan; Sri Lastuti; Suriya Ningsyih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research focuses on developing a digital-based learning evaluation tool using the Quizizz platform to assess the critical thinking abilities of fifth-grade students in the IPAS subject "Bumiku Sayang, Bumiku Malang." The study utilized a Research and Development (R&D) approach with the ADDIE framework (Analysis, Design, Development, Implementation, and Evaluation). The instrument underwent validation by subject matter and media experts, and its practicality and effectiveness were evaluated through questionnaires and pre-test/post-test analysis. Validation results indicated a high level of feasibility, with scores of 96% and 91% from content and media experts, respectively. The practicality test yielded scores of 92.2% from teachers and 94% from students, categorized as very practical. Meanwhile, effectiveness testing involving 20 students showed an increase in the average score from 36.95 (pre-test) to 72.95 (post-test), with an N-Gain score of 0.37, classified as moderate. These results suggest that the Quizizz-based evaluation instrument is valid, highly practical, and moderately effective in evaluating elementary students’ critical thinking skills.